Eksperimen Gamifikasi dalam Pembelajaran Etika Akuntansi: Analisis Pengaruh terhadap Kesadaran dan Pengambilan Keputusan Etis - Djauhar Edi Purnomo Djauhar; Khoirul Fatah (Universitas Muhammadiyah Jakarta, 2026)
Objectives: This research evaluates gamification effectiveness in improving ethical awareness and moral decision-making of Indonesian accounting students.Design/method/approach: Quantitative quasi-experimental design on accounting students from three Pekalongan universities (Stratified Random Sampling). Experimental group received gamification (interactive scenarios, rewards, competition); control group received conventional teaching. Pre-post test data via ethical sensitivity questionnaire and case simulations, analyzed using multiple linear regression in SPSS v24 (α=0.05; Cohen's d).Results/findings: Gamification group showed 24.2% increase in ethical awareness (p<0.001, Cohen's d=1.68) vs. 6.8% in control; moral decision-making improved by 12.8 points. Superior across all dimensions.Theoretical contribution: Reinforces experiential learning theory (Kolb, 1984), social constructivism (Vygotsky, 1978), and Four-Component Model (Rest, 1986) in accounting ethics education. Tested hypotheses (H1-H3) confirm gamification enhances ethical awareness and moral decision-making, with ethical awareness as mediator. Extends gamification literature (Deterding et al., 2011) in Indonesia's collectivist cultural context.Practical contribution: Integrate gamification into ethics/auditing curricula; train faculty and partner with industry for relevance.Limitations: Limited geographic scope (Pekalongan); short duration, simulation-based measurement only. Suggestion: national longitudinal studies.